Analisis kemampuan komunikasi (Communication Skill) mahasiswa dalam praktik mengajar peer teaching - Maura Dwi Amalia; Tuti Iriani; R. Eka Murtinugraha (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
Communication skills have a crucial role in the context of education, especially in the practice of teaching peer teaching in tertiary institutions. This study aims to analyze problems in the communication skills of prospective teacher students when practicing peer teaching in explaining skills. The research method uses a qualitative descriptive method with data analysis based on scientific journal literature studies and direct observation. The research was conducted on prospective teacher students who carried out peer teaching practices at Jakarta State University. The results of the study show that most of the prospective teacher students face problems in communication skills when practicing peer teaching. These problems include a lack of emphasis on intonation and articulation, as well as a lack of context in providing examples or illustrations of material. The suggested solution is the use of learning media that can improve the communication skills of prospective teacher students in explaining the material. This research is expected to provide insight for future researchers to develop the communication skills of prospective teacher students in the context of teaching practice.